Container Port Selection by Freight Forwarders in Central and Eastern Europe Hinterland: the Case of the Czech Republic - Petr Kolar; Jean-Paul Rodrigue (Naše More (Dubrovnik), 2018)
Containerization and port regionalization strategies have impacted the level of port competition in contestable hinterlands. However, the nature of this competition usually involves a single maritime range and well-defined transport corridors. The European context has underlined a complex dual range competition dynamic particularly involving the Northern Range and the Mediterranean. How these dynamics pan out in Central and Eastern Europe has received much less attention but will impact the growth prospects of ports on both ranges. This research study evaluates the importance of port selection factors by freight forwarders in the landlocked Czech Republic. It is based on a survey of key actors, particularly how specific carriers and ports are selected and which transport chains are used. The importance and stability of the factors are analysed within the framework of four constraint layers – the location layer; the infrastructure layer; the transport layer and the logistics layer. The key factors supporting the dominance of the port of Hamburg with the Czech Republic are discussed in addition with the potential of the North Adriatic Port Range to service this contestable hinterland. Hamburg is characterized with lower inland haulage costs, total shipment costs and the highest inland rail frequency compared to competing ports such as Bremerhaven or Koper. These factors are perceived as the key determinants by freight forwarders. Therefore, evidence underlines that the share of Hamburg is likely to remain unchanged in coming years and that Northern Range ports are dominant to service most of the Central and Eastern European hinterland. The paper supplements the literature with the analysis of primary data from business practitioners regarding port selection strategies by international trade intermediaries and fills the research gap for the region of Central and Eastern Europe.